2015
DOI: 10.1371/journal.pone.0117284
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Tissue and Serum MicroRNA Expression in Patients with Upper Urinary Tract Urothelial Cancer

Abstract: IntroductionMicroRNAs play an important role in many human malignancies; so far, their expression remains to be studied in upper urinary tract urothelial cancer (UUTUC).Materials and MethodsThe expression of eleven microRNAs (miR-10a, miR-21, miR-96, miR-135, miR-141, miR-182, miR-200b, miR-205, miR-429, miR-520b, miR-1244) formerly shown to be upregulated in urothelial bladder cancer were studied in corresponding normal and cancerous tissue samples of patients undergoing nephroureterectomy for UUTUC. Upregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…Scheffer et al (12) confirmed that the expression of 22 miRNAs in bladder cancer tissues was upregulated, including miR-96. Kriebel et al (11) reported that the expression of plasma miR-96 in patients with bladder cancer was significantly increased. Eissa et al (26) demonstrated that miR-96 was highly expressed in bladder cancer tissues, but not in benign bladder tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scheffer et al (12) confirmed that the expression of 22 miRNAs in bladder cancer tissues was upregulated, including miR-96. Kriebel et al (11) reported that the expression of plasma miR-96 in patients with bladder cancer was significantly increased. Eissa et al (26) demonstrated that miR-96 was highly expressed in bladder cancer tissues, but not in benign bladder tumors.…”
Section: Discussionmentioning
confidence: 99%
“…miR-96 is a conserved miRNA that may be involved in the occurrence and development of bladder cancer (9,10). Further research also demonstrated that miR-96 was highly expressed in bladder cancer tissue and the blood plasma obtained from patients with bladder cancer (11)(12)(13). Yamada et al (14) confirmed that miR-96 expression in urine samples from bladder urothelial carcinoma was significantly increased compared with that from healthy subjects.…”
Section: Introductionmentioning
confidence: 94%
“…Using deep-sequencing analysis, we found that miR-141-3p expression was decreased by 1.26-fold in early PCa compared to that in BPH (P < 0.05), and confirmed a similar 1.17-fold decrease in early PCa compared to that in BPH (P = 0.2053) by qRT-PCR. In addition, miR-141-3p expression levels vary in different tumors, with overexpression observed in bladder [16], urothelial [17], breast [18] [19], ovarian [20], endometrioid [21], cholangiocytes [22] and colorectal cancers [23] and NSCLC [24], while expression is downregulated in gastric cancer [25], hepatocellular carcinomas [26] [27], renal cell carcinoma [28], lymphatic metastatic pancreatic cancer [29], pituitary tumors [30], craniopharyngioma [31], head and neck cancer [32], osteosarcoma [33], and cutaneous T cell lymphoma [34]. These reports provide compelling evidence for a role of miR-141-3p as an oncogene or tumor suppressor in different tumors and at different stages.…”
Section: Discussionmentioning
confidence: 99%
“…These single-stranded sequences typically down regulate expression of mRNAs for tumorigenesis control, so they can potentially be utilized as cancer biomarkers and indicate the presence of an invasive tumor [8,9]. Detection can be applied to a clinical setting for minimal invasiveness because microRNAs can be observed in body fluids and they can maintain stability against changes in pH, RNase activity and temperature changes.…”
Section: Introductionmentioning
confidence: 99%
“…Detection can be applied to a clinical setting for minimal invasiveness because microRNAs can be observed in body fluids and they can maintain stability against changes in pH, RNase activity and temperature changes. As a result, microRNAs have been useful in diagnoses of bladder, kidney, prostate and testicular cancers [8,10]. There are still challenges for microRNAs in its applications, as it can be difficult to assay for miRNA and miRNAs may affect multiple genes that are not of interest [11].…”
Section: Introductionmentioning
confidence: 99%